Pengaruh Kesadaran, Keterjangkauan Biaya, Dukungan Regulasi, dan Tekanan Pasar Terhadap Niat UMKM Memperoleh Sertifikasi Halal - Satrio Abimanyu; Indra Indra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of halal awareness, cost affordability, regulatory support, and market pressure on the intention of culinary MSMEs in the Special Capital Region of Jakarta to obtain halal certification. This research employs a quantitative approach with a case study design. Data were collected through online questionnaires distributed to culinary MSME actors and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that partially, cost affordability and market pressure have a positive and significant effect on MSMEs’ intention to obtain halal certification, while halal awareness and regulatory support have a positive but insignificant effect. Market pressure is identified as the most dominant factor, suggesting that external drivers such as consumer demand and business competition are more influential than internal factors. Simultaneously, all variables significantly influence MSMEs’ intention to obtain halal certification. This study implies that increasing MSME participation in halal certification requires strategies that not only enhance awareness but also ensure affordable costs, simplify regulations, and strengthen the halal market ecosystem.